2018
DOI: 10.1109/tcomm.2017.2754280
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Generalized Spatial Modulation MIMO Over Measured 60GHz Indoor Channels

Abstract: In this paper, we study the capacity and symbol error probability (SEP) of generalized spatial modulation (GSM) multiple-input multiple-output (MIMO) using measured channels that are obtained by channel sounding in an indoor office environment at 60 GHz. Spatial modulation (SM) and GSM are emerging low-complexity MIMO schemes that have been extensively researched for low-GHz (below 6 GHz) communications. Recently, they have been considered and shown to be promising also for millimeter-wave (mmWave) communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 35 publications
0
49
0
Order By: Relevance
“…Complexity and Converge Analysis: The complexity of Algorithm 1 is dominated by the calculation of the gradients in (25) and (28). In each iteration, the calculation of the gradient Algorithm 1 Gradient ascent algorithm to maximize the SE lower bound 1: Initialize p (0) with p i = 1 |F | , i = 1, 2, · · · , |F|, λ (0) with λ ij = 1, j = 1, 2, · · · , N s , the halting criterion and the iteration number k = 0.…”
Section: Sementioning
confidence: 99%
See 1 more Smart Citation
“…Complexity and Converge Analysis: The complexity of Algorithm 1 is dominated by the calculation of the gradients in (25) and (28). In each iteration, the calculation of the gradient Algorithm 1 Gradient ascent algorithm to maximize the SE lower bound 1: Initialize p (0) with p i = 1 |F | , i = 1, 2, · · · , |F|, λ (0) with λ ij = 1, j = 1, 2, · · · , N s , the halting criterion and the iteration number k = 0.…”
Section: Sementioning
confidence: 99%
“…Compute the gradient ∇ λ f (p, λ) by using (28). 8: Carry out the projection to get ∆λ (k+1) by using (34).…”
mentioning
confidence: 99%
“…Previous studies on transmit spatial modulation are focused on conventional arrays: [6] analyzes solutions based on spatial modulation that exploit the diversity gain of the conventional antenna array and [7]- [14] provide preliminary results on the performance of transmit spatial modulation based on experimental data obtained with conventional antenna arrays. For more information on transmit spatial modulation, please refer to the survey papers [15]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive description of the main achievements and latest developments on SM research can be found in [6][7][8][9][10]. Some pioneering and recent experimental activities can be found in [11][12][13][14]. The research literature on *Correspondence: marco.direnzo@l2s.centralesupelec.fr 1 Laboratoire des Signaux et Systèmes, CNRS, CentraleSupelec, Univ Paris-Sud, Université Paris-Saclay, Plateau du Moulon, 91192 Gif-sur-Yvette, France Full list of author information is available at the end of the article SM is vast, and various issues have been tackled during the last few years, which include the analysis of the error probability [15], the design and analysis of transmit-diversity schemes [16,17], and the analysis and optimization of the achievable rate [18,19].…”
Section: Introductionmentioning
confidence: 99%